Effect of curcumin supplement or placebo in delayed onset muscle soreness: a systematic review and meta-analysis - Rattanaseth, Natthanichar (2023)
There are multiple strategies that have been suggested to attenuate delayed onset muscle soreness (DOMS). Curcumin has been shown to reduce exercise-induced oxidative stress (OS) and inflammation. However, currently, there is still controversy. This meta-analysis suggested that curcumin supplement reduced delayed onset muscle soreness and CK after exercise in 1, 2, 3, and 4 days when compared to placebo. However, TNF and IL were not affected by curcumin ingestion.